PERCEIVED COMPETENCE AND INTERVENING CONTEXT VARIABLES: THE PERSPECTIVE OF FEMININE GENDER (Fiep Bulletin - online, 2014)
The self-confidence demonstrated by the student is fundamental condition for the learning, and it has been object of researches about motivation in the area of physical education. The objective of this research is to characterize as pupils of feminine gender perceive the own competence and to verify relationships with context variables. The research is descriptive and correlational. The data were obtained through closed format Likert-scale questionnaire. The results show positive values of perceived competence and significant influence of the context variables related with the teachers' expectations and colleagues.
Keywords: perceived competence; gender; social support